Interventions to reduce social isolation and food insecurity in older adults: a systematic review - Sen, Keya; Kruse, Clemens Scott; Mileski, Michael; Ramamonjiarivelo, Zo (Frontiers in Nutrition, 2025)
IntroductionFood insecurity (FI) and social isolation (SI) are interconnected social determinants of health that disproportionately affect older adults. While FI and SI have been studied independently, their combined effects on malnutrition and quality of life (QoL) have not been adequately synthesized. This systematic review aimed to evaluate the efficacy of combined FI and SI interventions over the past decade, identify reported facilitators and barriers, and explore technology-based approaches to inform future research.MethodsThis study follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines and the Kruse Protocol. Peer-reviewed empirical studies were identified through systematic searches of PubMed, Web of Science, CINAHL, and ScienceDirect. Inclusion criteria targeted non-randomized controlled trials and community-based interventions focused on adults ≥ 65 years in the past 10 years. Six studies were examined using a narrative approach, supported by data matrices.ResultsThe studies suggested a relationship between FI and SI, among individuals with physical impairment, low income, and reduced access to community resources. Women were most affected. Although the studies were observational and varied in quality, findings indicated that FI and SI are associated with adverse health outcomes, such as depression, diabetes, cognitive decline, and reduced QoL. Promising interventions included commensality programs, food service apps, and technology supported community engagement, though barriers such as limited digital literacy, high costs, and infrastructure gaps persist.ConclusionThe review underscores the need for integrated interventions as the global older adult population grows. Due to limited methodological rigor, definitive conclusions cannot be drawn. Future research should use robust designs-randomized controlled trials, mixed methods, and longitudinal studies, and address structural barriers, including digital exclusion, to improve health outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420250418740.